Foam Splint versus Spica Cast-Early Mobilization after Hip Reconstructive Surgery in Children-Preliminary Data from a Prospective Randomized Clinical Trial - Lorenz Pisecky; Gerhard Großbötzl; Manuel Gahleitner; Christian Stadler; Stella Stevoska; Christina Haas; Tobias Gotterbarm; Matthias Christoph Michael Klotz (MDPI AG, 2022)
Background: Surgical hip joint reconstruction may be the method of choice for children and adolescents with developmental dysplasia of the hip (DDH), as well as neurogenic dislocation of the hip (NDH) and Legg-Calvé-Perthes disease (LCPD). Following pelvic surgery, immobilization using a spica cast is considered to be the gold standard, despite the fact that casting may cause complications, such as hygienic problems, skin lesions, neurological deficits, and rigidity of the adjacent joints. An alternative for postoperative immobilization is a foam splint. The purpose of this randomized controlled trial was to compare spica cast and foam splint immobilization after hip reconstruction in children and adolescents with DDH, NDH, and LCPD. Methods: In a prospective randomized clinical trial, children and adolescents (age: 4-14 years), who received hip reconstructive surgery (osteotomy of the ilium and proximal femur, open reduction, soft tissue techniques) for DDH, NDH, and LCPD were included. Patient recruitment, group allocation, surgery, and aftercare were carried out in a department for orthopaedic surgery in Central Europe. Standardized questionnaires SF-36 (Short Form-36), EQ-5D (Euro Quality of Life 5D and CPCHILD (Caregiver Priorities and Child Health Index of Life with Disabilities) were gathered before, six, and twelve weeks after surgery from each patient. Group one received a spica cast and group two a foam splint for a period of six weeks postoperatively. There was no difference in surgical treatment. Results: Twenty-one out of thirty planned patients were enrolled in the study. One patient had to be excluded because of a lack of compliance. All quality of life (QOL) scores showed a significant reduction at the 6-week follow-up compared to the preoperative assessment. After twelve weeks, the scores came back close to the preoperative values. A significant reduction was seen in the spica cast group pre- vs. postoperatively for the variables CPCHILD (81% vs. 64%, p = 0.001), EQ-5d (65% vs. 45%, p = 0.014), and SF-36 (85% vs. 74%, p = 0.004). The corresponding values for the foam splint group also presented a reduction for all scores, but without statistical significance. Complications occurred in five cases. Conclusions: Recent retrospective studies suggest that foam splint immobilization after hip reconstruction surgery is a safe and feasible method, promising fewer complications compared to spica casting. The preliminary results of this prospective randomized clinical trial show an improvement of the scores when using a foam splint compared to the conventionally used spica cast. Benefits for the patients may be fewer adverse events and no need to undergo a second round of anaesthesia for recasting. Data suggest higher patient and caretaker satisfaction in the foam splint group.